Spatial Structure and Long-Term Variations of The Ground-Level Temperature Variance - Kishcha, P. V.; Dmitrieva, I. V.
The global distribution of the ground-level temperature variance and its long-term variations have been investigated on the basis of the monthly mean temperature anomalies, obtained from ground-based and sea-borne meteorological observations from 1896 to 1990. Particular characteristics of the large-scale structure of the temperature variance have been found. There are three pronounced maxima in the global distribution of the temperature variance: in Central Siberia (60°≤φ≤75°N and 70°≤λ≤ 120°E), North America (60°≤φ≤75°N and −170°≤λ≤−120°E) and the Antarctica (50°≤φ≤65°S and −60°≤λ≤10°E, where φ and λ are the geographic latitude and longitude, respectively) and there are two minima: over the Atlantic and Pacific Ocean areas. The minimum over the Pacific is not as pronounced, as over the Atlantic. The spatial pattern of the ground-level temperature variance is, on the whole, stable, the positions of the zones of extrema remaining practically unchanged over a long time interval. These results indirectly corroborate the mechanism of solar impact on the properties of the low atmosphere by the modulation of the flux of galactic cosmic rays. The mechanism accounts for the spatial distribution of the temperature variance as a result of combined effect of solar activity and ocean. Long-term variations of the Siberian maximum of the ground-level temperature variance agree with the changing duration of the sunspot cycle, in contrast to the North American maximum.